The family Bignoniaceae in the Environmental Protection Area Serra Branca, Raso da Catarina, Jeremoabo, Bahia, Brazil - Silva, Luiza Regina; Castro, Milene Maria da Silva; Conceição, Adilva de Souza (Acta Scientiarum. Biological Sciences, 2016)
Bignoniaceae comprises 82 genera and 827 species distributed mostly in tropical and subtropical regions, with a few species in temperate climates, and is most diverse in South America. The Brazil is the center of diversity for the group, with about 406 species in 33 genera, of which 22 genera and 90 species occur in the Caatinga. The floristic survey of Bignoniaceae in the Environmental Protection Area Serra Branca included analysis of 31 specimens collected from August 2009 to February 2012. The analyses were supplemented with dried collections from the following herbaria: ALCB, HRB and HUEFS. Nine genera and 11 species were recorded: [Anemopaegma Mart ex DC; Bignonia L.; Cuspidaria DC.; Fridericia Mart.; Handroanthus Mattos; Jacaranda Juss; Lundia DC.; Mansoa DC. and Tabebuia Gomes ex DC.]. Fridericia was the most representative genus with three species. The taxonomic treatment includes a key for the identification, descriptions, illustrations, photos, data of the geographical distribution, reproductive phenology and comments about the species.